Research findings working with the p53 and Rb1 targeted osteosarcoma mouse model - Lu, Yaojuan (e-Century Publishing Corporation, 2014)
Osteosarcoma (OS) is the most common bone cancer in children and young adults. The etiology of osteosarcoma is currently unknown. Besides the predominant osteoblasts, the presence of cartilage forming chondrocytes within its tumor tissues suggests a role of chondrogenesis in osteosarcoma development. Runx2 is a master transcription factor both for osteoblast differentiation and for chondrocyte maturation. Interestingly, RUNX2 has been shown to directly interact with p53 and Rb1, two genes essential for osteosarcoma development in mice. However the in vivo relevance of Runx2 during osteosarcoma progression has not been elucidated. We have recently shown that targeting Runx2 expression in hypertrophic chondrocytes delays chondrocyte maturation. It has also been shown that osteoblast-specific deletion of p53 and Rb1 genes developed osteosarcoma in mice. Here, we report our recent research findings using these osteosarcoma mouse models as well as human osteosarcoma tissues. We have detected high-level RUNX2 expression in human osteoblastic osteosarcoma, while chondroblastic osteosarcoma is predominant with chondroid matrix. To minimize the effect of strain difference, we have backcrossed osterix-Cre mice onto congenic FVB/N genetic background. We also detected low-GC content (36%) in sequence around the floxed Rb1 gene and demonstrated that addition of BSA into the reaction system increases the efficiency of PCR genotyping of floxed Rb1 gene. Finally, we successfully generated multiple osteosarcoma mouse models with or without Runx2 transgenic background. These mice showed heterogeneous osteosarcoma phenotypes and marker gene expression. Characterization of these mice will facilitate understanding the role of Runx2 in osteosarcoma pathogenesis and possibly, for osteosarcoma treatment.